2015
DOI: 10.1016/j.colsurfb.2015.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric polymers as biomaterials for tissue engineering applications

Abstract: Tissue engineering often rely on scaffolds for supporting cell differentiation and growth. Novel paradigms for tissue engineering include the need of active or smart scaffolds in order to properly regenerate specific tissues. In particular, as electrical and electromechanical clues are among the most relevant ones in determining tissue functionality in tissues such as muscle and bone, among others, electroactive materials and, in particular, piezoelectric ones, show strong potential for novel tissue engineerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
353
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(365 citation statements)
references
References 158 publications
(85 reference statements)
5
353
0
7
Order By: Relevance
“…nonpolar α-phase, and polar β-, γ-, and δ-phases depending on the crystallization and processing conditions. It exhibits outstanding electroactive behavior, good chemical resistance and thermal stability [11,12]. So it finds wide applications in the electronic, biomedical and membrane industries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…nonpolar α-phase, and polar β-, γ-, and δ-phases depending on the crystallization and processing conditions. It exhibits outstanding electroactive behavior, good chemical resistance and thermal stability [11,12]. So it finds wide applications in the electronic, biomedical and membrane industries.…”
mentioning
confidence: 99%
“…Furthermore, the physical and tensile properties as well as antifouling performance of electrospun PVDF-Ag membranes are also studied for the purposes of comparison. The developed PVDF-based composites may also find a wide scope of application in the field of piezoelectric membranes for tissue engineering [12]. (NaNO 3 ), N, N-dimethylformamide (DMF), acetone were of analytical grade and used as received.…”
mentioning
confidence: 99%
“…Further, it has been shown that substrates based on PVDF have different influence on cell adhesion, proliferation and differentiation [7] depending on their morphology. Table 1 summarizes the different PVDF structures used as supports for cell viability studies.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional structures based on smart and functional biomaterials are increasingly playing an important role in TE applications once they do not work just as passive supports, but can also play a relevant role in the development of tissues and cells [7] by triggering/stimulating specific cues on both cells and tissues [8]. Also, in order to promote a better compatibility between cells and the biomaterial, different strategies have been used, including surface tailoring with biomimetic molecules such as peptides and adhesive proteins, tuning chemical and physical properties to produce similarity to native extra-cellular matrix (ECM), to modulate the surface and bulk properties or providing external therapeutic molecules in order to stimulate the surrounding cells and tissues [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these studies highlight the important role that charge plays in many biological processes and yet, this effect is often overlooked when considering replacement tissues. 54 Given the growing evidence that electromechanical cues are the most relevant for tissue engineering applications, 55 there is significant interest in producing active rather than conventional passive biomaterials.…”
Section: Effect Of Substrate Stiffnessmentioning
confidence: 99%